Financial Burden Borne by Laparoscopic Living Kidney Donors. Issue 9 (September 2017) - Wiseman, Jennifer F.; Jacobs, Cheryl L.; Larson, Dawn B.; Berglund, Danielle M.; Garvey, Catherine A.; Ibrahim, Hassan N.; Matas, Arthur J.
Abstract : Background: Living kidney donors have donation-related out-of-pocket costs (direct costs) and/or ongoing daily expenses while losing income (indirect costs). Yet there is little information about how much of a subjective burden these constitute for the donors. Methods: From December 2003 through December 2014, we surveyed donors 6 months postdonation to determine their financial burden related to donation (on a scale of 1 to 10) and what resources were used to cover expenses. Results: Of 1136 surveyed, 796 (70%) responded. Among respondents, mean age at donation was 43.6 ± 10.6 years, 64% were women, 96% were white, and 53% were related by blood to their recipient. Overall, 26% scored their financial burden as 5 or higher; 8% scored it as 8 or higher. Increased expenses were associated with a higher reported burden; however, significant burden was reported by some with no out-of-pocket expenses (presumably due to lost wages and continuing expenses). The burden was scored as 5 or higher by 27% of those employed outside the home (n = 660), 15% homemakers, 13% retirees, 40% students; 28% unemployed; and 26% whose occupation was unknown. Over half (51%) of those receiving a local or (means-tested) national grant still reported moderate to severe burden. Besides grants, donors used a variety of sources to help offset expenses: dipped into savings, borrowed from friends or family, took out a loan, and/or had a fundraiser. Those with the highest burden reported using the most additional sources. Conclusions: Donors should not have to incur costs or a financial burden to donate; the transplant community should strive to make donation financially neutral. Abstract : Living kidney donors have direct donation-related costs and/or ongoing daily expenses while losing income during donation, but donors should not have to incur costs or a financial burden to donate and the transplant community should strive to make donation financially neutral.